State Rumination: Associations with Emotional Stress Reactivity and Attention Biases. Issue 5 (December 2013) - LeMoult, Joelle; Arditte, Kimberly A.; D'Avanzato, Catherine; Joormann, Jutta
Within dysphoria, rumination has been identified as a particularly maladaptive emotion regulation strategy linked to prolonged negative affect and the onset of depressive episodes. Until now, the majority of research assessing naturally occurring rumination has utilized trait rumination measures; however, additional information may be obtained by assessing state rumination. The current study examined the association between state rumination and participants' emotional recovery from stress. In addition, biased attention toward emotional information was investigated as a mechanism that might underlie state rumination. Participants completed the exogenous cuing task to assess attentional engagement and disengagement from emotional facial expressions followed by a psychosocial stressor. State rumination and self-reported sadness were measured during the recovery period. As expected, state rumination was associated with less recovery in sadness scores, even after controlling for trait rumination and depressive symptoms. Moreover, within the high dysphoria group, participants who had more difficulty disengaging from emotional expressions reported higher levels of rumination in response to the stressor. Results highlight an important association between state rumination and individuals' recovery from stress, and suggest that difficulty disengaging attention from emotional expressions might be one mechanism underlying state rumination in dysphoria.